(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
تمّ عزل 72 عزلة جرثومية، منها (30) عزلة جرثومية مرتبطة بسطح الطحالب البحرية الخضراء Ulva fasciata Delile ، و(42) عزلة جرثومية من المياه البحرية، درست الفعالية المضادة لها تجاه (6) سلالات جرثومية بيئية مائية المنشأ، ثلاث سلالات سالبة صبغة غرام(Escherchia coli, Pseudomonas aeruginosa, Flavobacterium sp.) وثلاث سلالات إيجابية صبغة غرام (Staphylococcus aureus, Actinobacter sp., Bacillus sp.). أظهرت النتائج أن 20 عزلة مرتبطة بسطح الطحلب الأخضر وبنسبة 66.66% من عدد العزلات المدروسة أبدت فعالية مضادة عالية تجاه الجراثيم السالبة والإيجابية لصبغة غرام، بينما أقل نسبة 7.14% وتعادل (3) عزلات معزولة من المياه البحرية أبدت فعالية مضادة تجاه الجراثيم الإيجابية غرام فقط. وسجلت أربع عزلات من سطح الطحلب الأخضر فعالية في عدد من الجراثيم السالبة والإيجابية غرام معاً، أما العزلات الأخرى فكانت ذات تأثير مفرد، بينما العزلات الثلاث التي أظهرت فعالية مضادة للجراثيم من المياه البحرية كانت ذات تأثير مفرد لنوع جرثومي فقط من الجراثيم إيجابية غرام. اعتماداً على هذه النتائج، يمكن القول إن الجراثيم المرتبطة بسطح الطحلب تتميز بفعالية مضادة عالية تجاه طيف واسع من الجراثيم أكثر من الجراثيم التي تعيش حرة في المياه البحرية. We had isolated (72) strains of bacteria, (30) attached with green algae Ulva fasciata Delileand (42) from sea water, investigated for antibacterial activity against (6) environmental bacteria, three strains were Gram-negative (Escherchia coli, Pseudomonas aeruginosa, Flavobacterium sp.) and three strains were Gram-positive (Staphylococcus aureus, Actinobacter sp., Bacillus sp.) The results showed 20 isolates ofattached bacteriawith Ulva fasciata formed percentage 66.66% had high antibacterial activity against Gram-positiveand Gram-negative bacteria, while low percentage 7.14%(only 3) of isolates from sea water had antibacterial activity against Gram-positive bacteria only. Fourbacterial isolates attached with Ulv afasciata had showed effectiveness against anumber of Gram-positive and Gram-negative bacteria,while the other isolates had a single effect, and three isolates from sea water had only one single effect against a strain of Gram-positive bacteria only. Depending on these results, we can say that attached bacteria with marine green algae Ulva fasciata had broad-spectrum antibacterial activity more than thefree bacteria founded insea water.